Impact of Land Use/Cover Change (LUCC) on Carbon Storage in Zhaoqing by using the InVEST Model - Huang, Guangxing; Wang, Ruei-Yuan (International journal of Rural Development, Environment and Health Research, 2023)
Exploring the impact of Land Use/Cover Change (LUCC) on ecosystem carbon storage is of great significance for promoting low-carbon development. Based on the land cover data from 2000 to 2020 interpreted by remote sensing, this study uses the InVEST model to analyze the relationship between the spatial and temporal changes of carbon storage in the ecosystem of Zhaoqing City and land cover. The results show that: 1) In the past 20 years, the area of land cover types in Zhaoqing City has not changed much; the area of cultivated land, forest land, and grassland has decreased; and the area of water area, construction land, and unused land has increased. 2) The carbon storage volume in 2000, 2010, and 2020 were 296.74×106t, 297.00×106t, and 290.50×106t, respectively. Carbon storage increased at first and then decreased, showing an overall downward trend. 3) High carbon reserves are distributed in the central and northern mountainous areas of Zhaoqing City; medium carbon reserves are distributed in the western basin of Huaiji County; and low carbon reserves are distributed in the southern area of Zhaoqing. 4) From 2000 to 2010, the conversion between forest and grassland resulted in relatively stable carbon storage and an increase of 201,200 tons. The conversion of forest land and cultivated land into construction land and water has reduced carbon storage by 6.5745 million tons.